Never enough : the neuroscience and experience of addiction - Grisel, Judith (New York : Doubleday, 2019)
"Addiction is epidemic and catastrophic. With more than one in every five people over the age of fourteen addicted, drug abuse has been called the most formidable health problem worldwide. If we are not victims ourselves, we all know someone struggling with the merciless compulsion to alter their experience by changing how their brain functions. Drawing on years of research--as well as personal experience as a recovered addict--researcher and professor Judy Grisel has reached a fundamental conclusion: for the addict, there will never be enough drugs. The brain's capacity to learn and adapt is seemingly infinite, allowing it to counteract any regular disruption, including that caused by drugs. What begins as a normal state punctuated by periods of being high transforms over time into a state of desperate craving that is only temporarily subdued by a fix, explaining why addicts are unable to live either with or without their drug. One by one, Grisel shows how different drugs act on the brain, the kind of experiential effects they generate, and the specific reasons why each is so hard to kick. Grisel's insights lead to a better understanding of the brain's critical contributions to addictive behavior, and will help inform a more rational, coherent, and compassionate response to the epidemic in our homes and communities"--
Brain food -- Adaptation -- One salient example: THC -- Dream weavers -- The sledgehammer -- "Doctor please, some more of these": tranquilizers -- Pick me ups: stimulants -- Seeing clearly now: psychedelics -- If there's a will, there's a way -- Why me? -- Solving addiction.
Includes bibliographical references and index.
Keywords: Drug addiction -- Psychological aspects; Substance abuse -- Psychological aspects